CONCERN FOR THE PRESERVATION OF FORESTS IN SELECT LITERATURES AND CULTURES - Yadav, Prabhu Ray (International Journal of Research -GRANTHAALAYAH, 2025)
The manuscript discovers issues related to conserving forests and trees. While the role of the forest is glorified and highlighted in both literature and culture, what is important is how human beings maintain and protect it as an integral part of a healthy and well balanced eco-system. Deforestation is a burning issue today all over the world. Environmentally, sustainable development is inseparable from the way the forest with its impact on human life is treated rationally and pragmatically. In our own literature and culture that give meaning to life, the importance of the forest is recognized from many angles- religious, spiritual, social, cultural and emotional. A few instances would bear it out. Such is the aesthetic appeal of the forest that it is invariably felt and appreciated across the globe. It is, precisely speaking, indispensable for human existence. Usefulness of the forest can be realized and acknowledged only by respecting its laws not inconsistent with social norms and community ethos. People are indebted to the trees and forests for their relevance and contribution to the enrichment of human civilization as reflected in literature and culture. Besides, climatologists, in the context of climate change and its global repercussions such as floods, drought, landslides and rise in the level of the ocean threatening the very survival of low lying countries, have become increasingly conscious of the role that the woods play in shaping a safer world and making the planet earth a better place to live in. They are how the animated characters, who are found in myths and fairy tales, appeal to their narrative.